Geochemical Fraction Profile of Metal Cd, Pb and Zn on Sediments of Sidoarjo Mud Reclamation Area at Porong Sidoarjo Estuary - Ahmad Dody Setiadi; Barlah Rumhayati; Catur Retnaningdyah (Natural B, Journal of Health and Environmental Sciences, 2017)
Sediments of Porong River estuary suspected of containing a high concentration of heavy metals. the Sediment sample was collected from Porong Estuary river at two different location. The purposes of this study to determine the distribution concentration of metals geochemical fraction (Cd, Pb and Zn) at sediment Porong River estuary and correlation Against Physico-chemical properties of sediments. Analysis of sediment includes determining the concentration of Cd, Pb and Zn and determining of physicochemical properties of sediments such as pH, salinity, redox potential, cation exchange capacity, organic materials and sediment particles size. Extraction Method performed by BCR (Community Bureau of Reference) three steps sequential extraction, where a geochemical fraction of metals divided to 4 fractions, such acid soluble, reducible, oxidized and residual fractions. Research showed Zn has the highest concentration of each fraction and followed by Pb and Cd. Concentration of Zn in Fraction 1-4 ranged from 31,909 – 84,966 mg/Kg, Pb concentrations range 3,354 – 18,956 mg/Kg, whereas Cd concentrations range between 0,221 – 0,611 mg/Kg. The order of metals geochemical fraction concentration at Fraction 1, 2, 3 and 4 is Zn>Pb>Cd. There is some correlation between metals concentration against physicochemical properties of sediment. Where the physicochemical properties of sediment influence heavy metal content and concentration in the sediment of Porong River Sidoarjo.